TAFSIR BUGIS: PANDANGAN A.G. H. DAUD ISMAIL ATAS AYAT-AYAT AKIDAH - Muhammad Pais Ashari (LP2M Universitas PTIQ Jakarta, 2024)
The development of Qur'anic exegesis is an ongoing process. This serves as proof that the Qur'an remains a valid argument in every time and place. Scholars, in the process of developing their writings and interpretations, always adapt to the conditions of the local community. One of the prominent scholars in the Bugis region is AG. H. Daud Ismail. He was the first person in Bugis land to interpret the Qur'an in its entirety. This study employs a qualitative method, with the primary data source being the Tafsir Bahasa Bugis, a work by AG. H. Daud Ismail. The data is then analyzed descriptively and analytically to explain AG. H. Daud Ismail's perspective on creedal verses, particularly in response to the Bugis community, where many still adhere to ancestral beliefs such as Tau Lotang. The findings of this study reveal that AG. H. Daud Ismail not only developed Qur'anic exegesis but also engaged in da'wah by adapting to the local societal context, It also helps to understand the extent of his views when interpreting verses related to creed